2017
DOI: 10.1371/journal.pone.0169857
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cathepsin K in Late Stage of Tooth Germ Development and Its Function in Degrading Enamel Matrix Proteins in Mouse

Abstract: Cathepsin K (CTSK) is a member of cysteine proteinase family, and is predominantly expressed in osteoclastsfor degradationof bone matrix proteins. Given the similarity in physical properties of bone and dental mineralized tissues, including enamel, dentin and cementum, CTSK is likely to take part in mineralization process during odontogenesis. On the other hand, patients with pycnodysostosis caused by mutations of the CTSK gene displayedmultipledental abnormalities, such as hypoplasia of the enamel, obliterate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In the Balb/c model, first molars at P1 and P3 were at the late bell stage, and at P5 and P7 were at the secretory stage (Fig. 2 a–d), similar to a previous report (Lv et al 2011 ; Jiang et al 2017 ). The bell stage is a crucial stage where epithelial-mesenchymal interactions culminate in dramatic morphological and functional changes (Liu et al 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the Balb/c model, first molars at P1 and P3 were at the late bell stage, and at P5 and P7 were at the secretory stage (Fig. 2 a–d), similar to a previous report (Lv et al 2011 ; Jiang et al 2017 ). The bell stage is a crucial stage where epithelial-mesenchymal interactions culminate in dramatic morphological and functional changes (Liu et al 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, orthodontic appliances were needed in 30% of cases. Enamel quality has also to be taken into account when dealing with pycnodysostosis teeth, since CTSK has been proven to degrade the enamel matrix proteins in mice …”
Section: Discussionmentioning
confidence: 99%
“…Enamel quality has also to be taken into account when dealing with pycnodysostosis teeth, since CTSK has been proven to degrade the enamel matrix proteins in mice. 21 Hearing loss has been reported in some cases of pycnodysostosis [22][23][24][25][26] and was found in 36% of the subjects. All of them were mild and most of them did not need any treatment, except for two patients (10%) who were prescribed hearing aid.…”
Section: Patient Carementioning
confidence: 99%
“…It was reported that mutations of the CTSK gene displayed multiple dental abnormalities, such as hypoplasia of the enamel, obliterated pulp chambers, and periodontal disease, none of which were found among our studied patients [28]. The observed dental findings included a high caries index of 75%, which could be attributed to the crowding and malposition of teeth.…”
Section: Discussionmentioning
confidence: 52%